THE SOCIAL DISABILITY MODEL AND ITS IMPACT ON THEORY AND PRACTICE IN PSYCHOLOGY AND REHABILITATION - Nenadović, Vanja; Stanimirović, Dragana; Dimoski, Sanja (Specijalna edukacija i rehabilitacija, 2017)
This paper represents a review of genesis and basic assertions of the social disability model (SDM) and its impact on theory and practice in psychology and rehabilitation. With its view on disability as a form of oppression, SDM is focused on changing society. The developmental pathway from the earliest radical forms of the SDM to the recent more neutral orientation is shown. The study then turns to the changes in psychological theory and practice. The contribution of critical psychology in the struggle for social change is described at first. Afterwards, traditional psychology is criticized on several levels, with more contemporary views offered in the spirit of the new disability paradigm. These are shown as useful for assessment and intervention of disabled persons. The work is especially focused on psychological counselling, with a brief overview of theoretical aspects of counselling, compatible with the SDM and recommendations of different authors within this framework, concerning counselling practice in psychology and rehabilitation. Key words: social disability model, traditional psychology, critical psychology, psychological counselling, counselling in rehabilitation